The Relationship between Workload and Social Support with Nurse Job Satisfaction in Hospital Inpatient Room - Izzata, Nadia; Nursalam, Nursalam; Fitryasari, Rizki (Fundamental and Management Nursing Journal, 2021)
Introduction: Concern for good psychological condition of nurse regarding workload and social support in every job they do is an effective strategy to increase nurse job satisfaction. Nurse job satisfaction is important for the creation of better nurse performance. The purpose of the study was to explain the relationship between workload and social support with nurse job satisfaction in the inpatient room of RSUD Dr. Harjono Ponorogo.Method: The study used a descriptive correlational design with a cross sectional approach. The study population was 164 nurses in the inpatient room of RSUD Dr. Harjono Ponorogo. The sample size of 116 respondents was obtained by using cluster random sampling technique. The independent variables are workload and social support, while the dependent variable is nurse job satisfaction. The instruments used are workload questionnaire, social support questionnaire, and nurse job satisfaction questionnaire. Data analysis were used descriptive test and logistic regression test with a significant value of p â‰¤ 0.05.Results: There was a relationship between workload (p=0.000), social support (p=0,003), instrumental support (p=0.003), informational support (p=0.020), emotional support (p=0.004), appceciation support (p=0.019) with nurse job satisfaction.Conclusions: The light workload is characterized by a balance between the number of nurses and the demands of the existing task and good social support (instrumental support, informational support, emotional support, appreciation support), that nurses feel cared for and appreciated, can increase nurse job satisfaction. So that the performance of nurses increases and creates professional nursing services.